Representation of the Meaning of Love in the Song “Wa Anā Ma‘aka”: Tamyīz Ma‘nā al-Ḥubb Fī al-Aghānī "Wa Anā Ma‘akā" - Diantika, Devi Eka; Miftahul Mufid; Ahmad Amirul Kholid (An-Nahdah Al-'Arabiyah, 2025)
The song و أنا معك ("And I’m with You") by Mohammed Alsahli is a poetic and emotionally resonant love song that portrays love as a powerful, transformative, and unifying force. This study explores the representation of the semantic field of love in the song through a descriptive qualitative method combined with semantic analysis. The analysis focuses on key Arabic words and phrases found in the lyrics, such as حب (hubb – love), حبيبي (habibi – my beloved), قلبي (qalbi – my heart), عيوني (‘uyuni – my eyes), and روحي (ruhi – my soul). These expressions convey both literal and connotative meanings, reflecting the emotional depth and cultural significance of love in the Arabic tradition. The findings reveal two main thematic representations: love as a deep emotional attachment, and love as a life-changing, soul-connecting force. Each verse of the song contributes to this portrayal—emphasizing completeness in companionship, the struggle of separation, and the merging of emotional perspectives. Beyond its lyrical beauty, the song embodies key values of Arab cultural expression, where love is not only romantic but also existential. This study contributes to the understanding of Arabic semantic structures and highlights the importance of music as a medium for expressing complex cultural emotions.   عَدّ أغنية و أنا معك ("وأنا معك") للفنّان محمد السهلي عملاً غنائياً عاطفياً وشعرياً، تُصوِّر الحبّ باعتباره قوّة هائلة، تحوّلية وموحِّدة. تهدف هذه الدراسة إلى استكشاف تمثيل الحقل الدلالي للحبّ في هذه الأغنية من خلال المنهج الوصفي النوعي المقرون بالتحليل الدلالي. ويركّز التحليل على الكلمات والتعابير الرئيسة في النص الغنائي، مثل: حب (ḥubb – الحب)، حبيبي (ḥabībī – حبيبي)، قلبي (qalbī – قلبي)، عيوني (‘uyūnī – عيوني)، و روحي (rūḥī – روحي). وتنقل هذه التعابير معانيَ حرفية وأخرى إيحائية، بما يعكس عمق العاطفة وأهمية الحبّ في الثقافة العربية. وتكشف النتائج عن تمثيلين موضوعيين رئيسين: أوّلهما الحبّ كارتباط عاطفي عميق، وثانيهما الحبّ كقوّة تغيّر الحياة وتصل الأرواح بعضها ببعض. ويسهم كلّ مقطع من الأغنية في هذا التصوير، حيث يُبرز الكمال في الرفقة، ومعاناة الفراق، واندماج الرؤى العاطفية. وبالإضافة إلى جمال النصوص الشعرية، تُجسّد الأغنية قيماً أساسية من التعبير الثقافي العربي، حيث يظهر الحبّ ليس فقط كعاطفة رومانسية، بل كحقيقة وجودية. وتُسهم هذه الدراسة في فهم البُنى الدلالية في اللغة العربية، وتؤكّد على دور الموسيقى كوسيلة للتعبير عن الانفعالات الثقافية المعقّدة.   Lagu و أنا معك ("Dan Aku Bersamamu") karya Mohammed Alsahli merupakan sebuah lagu cinta yang puitis dan sarat emosi, menggambarkan cinta sebagai kekuatan yang dahsyat, transformatif, dan mempersatukan. Penelitian ini mengeksplorasi representasi medan makna cinta dalam lagu tersebut melalui metode deskriptif kualitatif yang dipadukan dengan analisis semantik. Analisis difokuskan pada kata-kata dan ungkapan kunci dalam bahasa Arab yang terdapat dalam lirik, seperti حب (ḥubb – cinta), حبيبي (ḥabībī – kekasihku), قلبي (qalbī – hatiku), عيوني (‘uyūnī – mataku), dan روحي (rūḥī – jiwaku). Ungkapan-ungkapan ini menyampaikan makna denotatif maupun konotatif, yang mencerminkan kedalaman emosional serta signifikansi budaya cinta dalam tradisi Arab. Hasil penelitian mengungkapkan dua representasi tematik utama: cinta sebagai ikatan emosional yang mendalam, dan cinta sebagai kekuatan yang mengubah hidup serta menghubungkan jiwa. Setiap bait lagu berkontribusi pada penggambaran tersebut—menekankan kesempurnaan dalam kebersamaan, pergulatan karena perpisahan, serta penyatuan perspektif emosional. Lebih dari sekadar keindahan lirik, lagu ini mewujudkan nilai-nilai penting dalam ekspresi budaya Arab, di mana cinta tidak hanya bersifat romantis, tetapi juga eksistensial. Penelitian ini memberikan kontribusi pada pemahaman struktur semantik bahasa Arab sekaligus menyoroti pentingnya musik sebagai media untuk mengekspresikan emosi kultural yang kompleks.